A population-based cohort study of stillbirth among twins in Lusaka, Zambia. Issue 1 (July 2015) - Stringer, Elizabeth M.; Chibwesha, Carla; Stoner, Marie; Vwalika, Bellington; Joseph, Jessica; Chi, Benjamin H.; Kaunda, Eugene; Goodnight, William; Stringer, Jeffrey S.A.
Abstract: Objective: To determine rates of stillbirth and the associated risk factors for stillbirth among twins delivered in Lusaka, Zambia. Methods: A retrospective cohort analysis was conducted of singletons and twins delivered at 26 public sector facilities between February 1, 2006, and May 31, 2013. Data were obtained from the Zambian Electronic Perinatal Record System. Risk of stillbirth was estimated using logistic regression. Results: Overall, 260 657 singletons and 4021 twin pairs were included. There were 5105 stillbirths; 317 twins were stillborn. The crude stillbirth rate for twins was 39.4 per 1000 births (95% confidence interval [CI] 35.2–43.7) whereas the rate for singletons was 18.4 per 1000 births (95% CI 17.9–18.9; P < 0.001). Factors associated with stillbirth among twins were increased interval between delivery (> 60 minutes), low birth weight (< 2500 g), birth order (being the second-born), and difference in birth weights (> 30% discordance). Conclusion: Twins were at an increased risk of stillbirth. Improved understanding of factors associated with stillbirth in this population could help to improve perinatal outcomes globally.